DNA methylation of COMT, DRD2 and DRD4 genes in schizophrenic patients - Nour El Huda Abd Rahim (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
A variety of evidences of genetic factors had been implicated in schizophrenia but the identification of specific gene has proven to be difficult. Based on the dopaminergic hypothesis in schizophrenia, most of the research conducted has focused on genes regulating dopaminergic function. Accumulating evidences suggest the role of DNA methylation in the patho-aetiology of schizophrenia and there are several confounding factors that may contribute to the DNA methylation. Therefore, the aims of the study are to assess the DNA methylation of COMT, DRD2 and DRD4 genes in the peripheral blood and their associations with the psycho-pathological symptoms, antipsychotic drugs treatment and BMI and the effect on the gene expression. The case control cross sectional study consisted of 138 schizophrenia patients from the Psychiatry Clinic, Hospital Kuantan Ampuan Afzan, Kuantan Pahang and 132 healthy controls from Kuantan district. The genomic DNA samples from the peripheral blood were bisulfite converted. The COMT, DRD2 and DRD4 DNA methylation levels were quantitatively measured by using the MethyLight Taqman® assay and normalized with the ALU reference control to give the percentage methylation ratio. The psycho-pathological symptoms were assessed using the Positive and Negative Syndrome Scale (PANSS). The demographic data were calculated using descriptive statistics while parametric variables were compared using independent samples t-test or analysis of covariance, and the regression analysis was used for prediction. The independent-t test showed significant lower DNA methylation of COMT (p<0.001), DRD2 (p=0.001) and DRD4 (p=0.001) in schizophrenia patients. The lower methylations of each gene were also significant in males and females. There were inverse relationship between the DNA methylation of the dopamine associated genes and psycho-pathological symptoms. COMT, DRD2 and DRD4 DNA methylation were significantly correlated (p <0.002) with, and predictors of the Excitement and the Depressed subdomains of PANSS. In addition DRD4 DNA methylation was highly correlated (p=0.010) and significant predictor of the Disorganization subdomain. There were higher methylations of COMT and DRD2 in typical antipsychotics-treated patients (p≤0.05). The overweight BMI schizophrenia patients showed higher COMT and DRD2 DNA methylation (p≤0.05). In conclusion, this study strongly support the possible role of COMT, DRD2 and DRD4 DNA methylation could contribute in the patho-aetiology of schizophrenia. The relationship between the DNA methylation of dopamine-associated genes with the psycho-pathological symptoms and the antipsychotics used might indicate the epigenetic role of genes methylation in the manifestation of schizophrenia and their possible role in the mechanisms of action of antipsychotic drugs. The association of the DNA methylation of COMT, DRD2 and DRD4 with BMI support the theories that obesity in schizophrenia is multifactorial and DNA methylation could be one of the contributing factors.